Responses of selected mungbean (Vigna radiata L.) varieties to boron fertilization - Tania, Sania Afrin; Uddin, F M Jamil; Sarkar, Md Abdur Rahman (Fundamental and Applied Agriculture, 2018)
This experiment was carried out during the period of March–June 2016 to evaluate the influence of variety and boron (B) levels on the growth and yield performance of four summer mungbean (Vigna radiata L.) varieties. The experimental treatments consisted of four mungbean varieties viz. BARI Mung–2, BARI Mung–6, Binamoog–5 and Binamoog–7 and four doses of boron viz. 0, 0.5, 1.0 and 1.5 kg ha−1. The experiment was arranged by randomized complete block design and replicated thrice. Variety BARI Mung–6 showed superiority to other varieties regarding pods plant−1, pod length, and 1000-grains weight which resulted in the highest seed yield (1.86 t ha−1). The lowest pods plant−1 in Binamoog–7, pods length and 1000-grain weight in BARI Mung–2, number of grains pod−1, and seed yield (1.25 t ha−1) stover yield and harvest index were found in Binamoog–5. Results revealed that the 1.0 kg ha−1 was superior to other doses of boron in respect of pods plant−1, pod length, number of grains pod−1, 1000-grain weight, seed yield, and stover yield as well as harvest index. The lowest seed yield (0.87 t ha−1) was found from control treatment. Variety BARI Mung–6 was grown with 1.0 kg ha−1 boron showed best performance to other interactions of variety and boron doses regarding pod length, number of pods plant−1, number of grains pod−1, number of grains plant−1, 1000-grain weight and seed yield (1.66 t ha−1).